Asymmetries of leadership: Agency, response and reason. (February 2020) - Tomkins, Leah; Hartley, Jean; Bristow, Alexandra
Drawing on empirical data from an action research project in policing, we propose that the power relations of leadership unfold in asymmetries of agency, response and reason: Leaders both expect and experience more responsibility than control; more blame than praise; and interpretations of failure – both their own and others' – based more on personal fault than on situational or task complexity. We focus, therefore, on power asymmetry not in the sense of structural inequality between leaders and followers, but rather, as constellations of incongruity, imbalance and unevenness which circumscribe leaders' actions, choices, relationships and feelings about their work. From this perspective, privilege and disadvantage are not polar opposites reflecting the powerful versus the powerless; instead, they are intimately interwoven within leadership experience. The asymmetries of police leadership involve an intermingling of the necessary and the impossible; a decoupling of failure from irresponsibility; resilience at the prospect of being blamed for success as readily as for failure; and containment of society's unresolved crises of responsibility, anxiety and risk. We crystallise this as a paradox of transparency and occlusion – of openness and closedness – in which police leaders are scrutinised by, and answerable to, those whom they must also protect, including from having to bear the full burden of knowledge of the dangers of the world. We reflect on the implications of this not just within policing, but for critical understandings of the power of leadership more generally.